Design and Development of a GAS-Based E-Commerce Application with UI/UX Optimization Using a User-Centered Design Approach - Wahyu Nofiyan Hadi; Umi Diantika Susilowati; Anisa Nurul Wilda; Moh. Fadel; Muhammad Ichsan; Syifa Ayu Via Mika Bahrul; Rojil Ghufron; Arya Dwi Nugraha; Yoga Ari Tofan (International Journal of Computer, Network Security and Information System, 2026)
Micro, Small, and Medium Enterprises (MSMEs) offering custom embroidery and tailoring services face significant challenges with digitizing orders. Conventional e-commerce platforms primarily serve ready-made products. They lack flexibility for custom workflow options, like letting customers submit their own designs or bring in clothing for embroidery. MSMEs are often burdened by ongoing server maintenance costs. This study seeks to design and implement a web-based e-commerce information system using a User-Centered Design (UCD) approach. The case study is applied to Cindy Bordir in Probolinggo. To address the research gap regarding high-cost and rigid platforms, the application introduces a zero-cost serverless architecture. This uses Google Apps Script (GAS) and Google Spreadsheet as the database. A